A Computational Study of the Kinetics and Mechanism for the C2H3 + CH3OH Reaction. Issue 12 (23rd October 2015) - Chen, Chaoxu; Song, Jinou; Song, Chonglin; Lv, Gang
ABSTRACT: The mechanism for the C2 H3 + CH3 OH reaction has been investigated by the Gaussian‐4 (G4) method based on the geometric parameters of the stationary points optimized at the B3LYP/6–31G(2df, p) level of theory. Four transition states have been identified for the production of C2 H4 + CH3 O (TSR/P1), C2 H4 + CH2 OH (TSR/P2), C2 H3 OH + CH3 (TSR/P3), and C2 H3 OCH3 + H (TSR/P4) with the corresponding barriers 8.48, 9.25, 37.62, and 34.95 kcal/mol at the G4 level of theory, respectively. The rate constants and branching ratios for the two lower energy H‐abstraction reactions were calculated using canonical variational transition state theory with the Eckart tunneling correction at the temperature range 300–2500 K. The predicted rate constants have been compared with existing literature data, and the uncertainty has been discussed. The branching ratio calculation suggests that the channel producing CH3 O is dominant up to about 1070 K, above which the channel producing CH2 OH becomes very competitive.